2017
DOI: 10.1097/md.0000000000006481
|View full text |Cite
|
Sign up to set email alerts
|

Low hospital referral rates of school scoliosis screening positives in an urban district of mainland China

Abstract: Significant prevalence rates of adolescent scoliosis in China were suggested in previous studies. However, school screenings for adolescent scoliosis have been suspended due to low rates of positive detection under the past screening system in China. The present study was undertaken to screen for adolescent scoliosis in middle school students under a modern assessment system in a district of Shanghai. We performed a population-based, cross-sectional study of a middle school scoliosis screening program in the J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…The assessment revealed that diseases of the musculoskeletal system and connective tissue constantly held the 1 st rank place in the structure of morbidity among 4 th grade children as well as middle and senior school children. These results are in line with data provided by foreign and domestic researchers [2,3,[16][17][18][19][20][21].…”
Section: __________________________supporting
confidence: 91%
“…The assessment revealed that diseases of the musculoskeletal system and connective tissue constantly held the 1 st rank place in the structure of morbidity among 4 th grade children as well as middle and senior school children. These results are in line with data provided by foreign and domestic researchers [2,3,[16][17][18][19][20][21].…”
Section: __________________________supporting
confidence: 91%
“…School screening policies began in the 1960s in the USA. [ 10 14 21 ] Later, some countries such as Japan, Hong Kong or South Africa made it compulsory in their school health policy,[ 5 14 22 ] which enabled them to know the prevalence of IS but also analyse the cost related to screening. [ 1 ] However, the different prevalence reported in the literature must be interpreted with caution because the definition of scoliosis and the study populations are not uniform.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the data of modern foreign literature [12,13,20,23], the incidence indicators of scoliosis (72.5 %) and postural disorder (75.0 %) in school-aged children coincided.…”
Section: Original Researchmentioning
confidence: 91%
“…Among 79 122 schoolchildren in the city of Wuxi, eastern China, adolescent idiopathic scoliosis was found in 2.4 %, and in the Shanghai area, among 5327 investigated secondary school students (grades 6-8), scoliosis was diagnosed by screening method in 520 children (9.76 %) and spinal X-ray was performed in 102 of them (33.9 %) [12,13].…”
Section: Original Researchmentioning
confidence: 99%